2011
DOI: 10.1093/geront/gnr049
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Older Family Members in Providing Social Resources and Promoting Cancer Screening in Families With a Hereditary Cancer Syndrome

Abstract: Engaging older network members in health interventions to facilitate screening behaviors and emotional well-being of younger members within families affected by inherited conditions may be beneficial. Findings can be used to empower older individuals about their important social roles in enhancing the well-being of their family members and to inform younger individuals about their older relatives' resourcefulness to facilitate positive social interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 27 publications
3
27
0
4
Order By: Relevance
“…Key motivators for engaging in genetic counselling were: to obtain information conducive to act for illness prevention and early detection (through surveillance measures for early detection and prophylactic risk reducing interventions); and to enable relatives (especially descendants) to benefit from genetic counselling. Other factors emerged as relevant: older members were reported as encouragers for the younger generation in seeking testing and screening behaviours, which is consistent with previous findings [63]; and to make sense of the origins of the disease in the family. Therefore, engagement in genetic counselling entwines individual and interpersonal motivators, led by the influence of older generations, a commitment to monitor risk appropriately and to act to preserve other relatives' health, and to know the familial routes of the risk in the family.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Key motivators for engaging in genetic counselling were: to obtain information conducive to act for illness prevention and early detection (through surveillance measures for early detection and prophylactic risk reducing interventions); and to enable relatives (especially descendants) to benefit from genetic counselling. Other factors emerged as relevant: older members were reported as encouragers for the younger generation in seeking testing and screening behaviours, which is consistent with previous findings [63]; and to make sense of the origins of the disease in the family. Therefore, engagement in genetic counselling entwines individual and interpersonal motivators, led by the influence of older generations, a commitment to monitor risk appropriately and to act to preserve other relatives' health, and to know the familial routes of the risk in the family.…”
Section: Discussionsupporting
confidence: 86%
“…The following familial roles regarding the passing on of genetic risk information emerged: disseminators were also information gatherers; disseminators tended to have a personal history of cancer and were typically the proband (the first person in the family to undergo testing); blockers (absent at the interviews) to the transmission of information were also mentioned; older relatives were the ''keepers'' of families' health history, described as valuable resources and as providers of privileged health information, namely for family risk assessment. These results were generally consistent with literature [63,66]. Families tended to mention that communication about genetic risk occurred openly within the nuclear family and among first degree relatives, whereas problems arose in communicating with extended family members (even though first degree relatives are here included) due to emotional distance, conflicts or the wish not to bother or scare them [67,68].…”
Section: Discussionsupporting
confidence: 82%
“…These are standard items used to measure encouragement in studies of personal networks, and have been found to be associated with a range of actual and intended health behaviors (Ashida et al, 2010, 2012; Ersig et al, 2009), as well as associated with other communication and support relationships in families (Ashida et al, 2011), providing support for construct validity. Four categories of parent–child dyads were identified from these responses: (1) dyads who shared no encouragement, (2) dyads in which the parent encouraged the child to do PA, (3) dyads in which the child encouraged the parent to do PA, and (4) dyads with reciprocal encouragement (parent and child encourage each other).…”
Section: Methodsmentioning
confidence: 99%
“…Os estudos indicam o envolvimento de elementos mais velhos no encorajamento à realização de rastreamentos e a sua associação a níveis mais elevados de intenção de adesão 9 . Os mais velhos surgem ainda como fonte de segurança e aconselhamento, dando informação sobre saúde, apoio e influência social, especialmente junto dos mais jovens 10 . A literatura evidencia também a sua importância na eficaz disseminação da história de saúde na rede familiar 7,9,11 .…”
Section: Introductionunclassified